2022
DOI: 10.5603/pjnns.a2022.0010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of age in patients with acute ischaemic stroke treated with intravenous thrombolysis

Abstract: Aim of the study. To assess the influence of age on long-term functional outcome in patients with acute ischaemic stroke (AIS) treated with intravenous thrombolysis (IVT). Material and methods.We performed retrospective analysis of 362 AIS patients treated with IVT or IVT and subsequent mechanical thrombectomy in the University Hospital in Krakow, Poland. Patients were categorised into four subgroups by age: (I) below the age of 60, (II) 60 to 69, (III) 70 to 79, and (IV) 80 or more. The outcomes were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(99 reference statements)
1
1
0
Order By: Relevance
“…Patients with stroke in old age have shown a higher risk of functional dependence and poorer functional recovery. This would affect their eating ability, in addition to the natural changes of aging [25,26]. Our study also revealed that age was a significantly associated factor for malnutrition in both acute and subacute stroke phases.…”
Section: Discussionsupporting
confidence: 51%
“…Patients with stroke in old age have shown a higher risk of functional dependence and poorer functional recovery. This would affect their eating ability, in addition to the natural changes of aging [25,26]. Our study also revealed that age was a significantly associated factor for malnutrition in both acute and subacute stroke phases.…”
Section: Discussionsupporting
confidence: 51%
“…The inclusion criteria for the study were admission within 12 h after AIS onset, a previous Barthel score ≥ 85 (as signs of disability before stroke are independent risk factors for worse prognosis, especially in elderly AIS patients treated with intravenous thrombolysis [20]), and the absence of stupor or coma.…”
Section: Data Collectionmentioning
confidence: 99%